Pengaruh Metode Fermentasi dan Lama Penyangraian Terhadap Cita Rasa Kopi Tuni Asal Maluku - Lessy, Septya Ningsih; Ega, La; Breemer, Rachel (Universitas Pattimura, 2023)
Coffee is a plantation product that has a fairly high economic value in one of the other plantation crops so it has an important role in improving the country's economy. The purpose of this study was to determine the proper fermentation method and roasting time for the quality of Tuni coffee. This study used a completely randomized design factorial which consisted of 2 factors: the first factor was the influence of the type of fermentation (P) with 2 treatment levels P1 = 48 hours wet fermentation, P2 = 48 hours dry fermentation, and the second factor affected roasting time with 3 treatment level T1 = 10 minute roasting time: 180°C temperature, T2 = 20 minute roasting time: 180°C temperature, T3 = 30 minute roasting time: 180°C temperature. 30 minutes of roasting time is the best treatment based on chemical characteristics including 4.14% moisture content, and 0.143% caffeine content. While the best treatment based on interaction was in the dry fermentation method and 30 minutes of roasting time was found at a protein content of 16.14%. Based on the organoleptic test, the dry fermentation treatment and roasting time of 20 minutes was the best treatment including color, taste, aroma, and overall.